Numerical Solution of Kawahara Equation Using Neural Network - Murad, Shayma A.; Melhum, Amera I.; Omar, Lamya A. (Science Journal of University of Zakho, 2014)
An artificial neural network technique is proposed in this research to solve the well-known partial differential equations of the types: Kawahara and modified Kawahara equations. The mathematical model of the equation was developed with the help of artificial neural networks. The construction requires imposing certain constrains on the values of the input, bias and output weights, and on the attribution of certain roles of each aforementioned parameters. The results obtained from the proposed technique were very accurate, simple and convenient. Moreover, the comparison between the approximated solutions and the exact one has done. This comparison found them in a good agreement with each other due to of superior properties of the Neural Network.
Keywords: Kawahara Equation; Modified Kawahara Equation; Artificial Neural Network